The Means of Sea Transportation - Budi Mantoro; Ong Argo Victoria (IWJ : Inland Waterways Journal, 2020)
Sea transportation as part of the national transportation system needs to be developed in order to realize an archipelago insight that unites all regions of Indonesia, including the archipelago seas as a national territory unit. The development of sea transportation must be able to drive Indonesia's development. Sea transportation makes a huge contribution to the world economy where the transportation of goods is the most important part of the sea transportation business where more than seven billion tonnes of goods are sent by sea every year. The effectiveness of shipping operations will reduce operating costs which will have a big impact on both consumers and transportation service providers themselves. It should be noted that the contribution of sea transportation is becoming increasingly important because the value of the costs incurred is the smallest when compared to the cost of land or air transportation. In addition, efficiency in the transportation and distribution process is one of the important things because the proportion of transportation costs can reach 66% of the total logistics costs. Considering the geographical condition of Indonesia as the largest archipelagic country in the world and two-thirds of its territory is water, Indonesia needs a large enough mass sea transportation to support the distribution of goods and to mobilize passengers. An effective and efficient transportation system that is integrated between transportation modes is essential to create a reliable and dynamic national distribution pattern. It cannot be denied that sea transportation in an archipelagic country such as Indonesia has become the main backbone of the movement of large-scale distribution of goods using ships. From an economic and business perspective, the use of transportation by ships is more effective and has great benefits. So that with the existence of marine transportation infrastructure for moving goods from one place to another, it is hoped that the economic activities of the community will be followed by a positive impact in improving the economy of a region.